E-waste management and resources recovery in France. Issue 10 (October 2015) - Vadoudi, Kiyan; Kim, Junbeum; Laratte, Bertrand; Lee, Seung-Jin; Troussier, Nadège
There are various issues of concern regarding electronic waste management, such as the toxicity of hazardous materials and the collection, recycling and recovery of useful resources. To understand the fate of electronic waste after collection and recycling, a products and materials flow analysis should be performed. This is a critical need, as material resources are becoming increasingly scarce and recycling may be able to provide secondary sources for new materials in the future. In this study, we investigate electronic waste systems, specifically the resource recovery or recycling aspects, as well as mapping electronic waste flows based on collection data in France. Approximately 1, 588, 453 t of new electrical and electronic equipment were sold in the French market in 2010. Of this amount, 430, 000 t of electronic waste were collected, with the remaining 1, 128, 444 t remaining in stock. Furthermore, the total recycled amounts were 354, 106 t and 11, 396 t, respectively. The main electronic waste materials were ferrous metals (37%), plastic (22%), aluminium (12%), copper (11%) and glass (7%). This study will contribute to developing sustainable electronic waste and resource recycling systems in France.